Analisis Implementasi Standard Operating Procedure (SOP) Apron Movement Control dalam Pelayanan Pemanduan Kendaraan Di Bandar Udara Sultan Mahmud Badaruddin II Palembang - Dimas Fakhrurozi; Septiyani Putri Astutik (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In serving aviation activities on the air side, the role and supervision required in managing airside traffic from the Apron Movement Control Unit or AMC. When monitoring and providing services on the air side, the AMC unit must comply with the main tasks and functions that have been determined in order to achieve the monitoring and service tasks in accordance with the Standard Operating Procedure (SOP) that has been determined in article 217 paragraph (1) of Law Number 1 of 2009 concerning flight. This research aims to find out how the SOP for Apron Movement Control (AMC) Personnel is implemented and what obstacles are faced by AMC Personnel in vehicle piloting services (VVIP vehicles, project vehicles, criminal vehicles) at Palembang's Sultan Mahmud Badaruddin II Airport. This research uses a qualitative approach with types and sources of data, namely primary data and secondary data. This research was carried out from August 2023 to February 2024 at Palembang's Sultan Mahmud Badaruddin II Airport. The results of this research are that the implementation of the Standard Operating Procedure (SOP) for Apron Movement Control in the Vehicle Guidance Service at Sultan Mahmud Badaruddin II Airport in Palembang went well and smoothly, apart from that there were several obstacles such as miscommunication between the AMC and other related parties. resulting in information being received repeatedly so that the information received by the AMC becomes inaccurate. And the lack of harmony between officials when leaving an event held airside can result in a lack of effectiveness in using the FOLLOW ME car.